2022
DOI: 10.1158/1078-0432.ccr-22-2060
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Mifepristone Treatment in Patients with Breast Cancer Selected by the Progesterone Receptor Isoform Ratio: Results from the MIPRA Trial

Abstract: Purpose: Preclinical data suggest that antiprogestins inhibit the growth of luminal breast carcinomas that express higher levels of progesterone receptor isoform A (PRA) than isoform B (PRB). Thus, we designed a pre-surgical window of opportunity trial to determine the therapeutic effects of mifepristone in patients with breast cancer based on their high PRA/PRB isoform ratio (MIPRA; NCT02651844). Patients and Methods: Twenty patients with luminal breast carcinomas with PRA/PRB>1.5 (determined by wester… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…In 1982, mifepristone was reported as the first selective progesterone receptor modulator . Current studies for understanding the mechanism of action of mifepristone are changing our views on the drug beyond its abortifacient scope . Mifepristone has been found to have potential clinical applications in gynecological therapies, such as endometriosis and uterine fibroids .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1982, mifepristone was reported as the first selective progesterone receptor modulator . Current studies for understanding the mechanism of action of mifepristone are changing our views on the drug beyond its abortifacient scope . Mifepristone has been found to have potential clinical applications in gynecological therapies, such as endometriosis and uterine fibroids .…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 Current studies for understanding the mechanism of action of mifepristone are changing our views on the drug beyond its abortifacient scope. 18 , 19 , 20 Mifepristone has been found to have potential clinical applications in gynecological therapies, such as endometriosis and uterine fibroids. 21 , 22 A previous study indicated that mifepristone treatment inhibited the development of adenomyosis in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Mifepristone, ulipristal acetate, and telapristone acetate have been shown to decrease cell proliferation, inhibit cell cycle progression, and increase apoptosis of breast cancer cell lines (115,116). Additionally, preclinical studies have also revealed that mifepristone and telapristone acetate can inhibit angiogenesis and migration of breast cancer cells in vivo (117,118). Recently, the phase I MIPRA trial exploring the effects of mifepristone in women with breast cancer pre-selected for high PR-A:PR-B ratios in the tumor demonstrated a significant decrease in Ki-67 proliferation marker with an increase in Cleaved caspase 3 compared to baseline expression after two weeks of treatment (119).…”
Section: Selective Progesterone Receptor Modulatorsmentioning
confidence: 99%
“…HR-positive breast tumors depend on activated ERα to support their growth, and thus, most endocrine therapies (ET) target the ER signaling pathway, usually blocking ERα transcriptional activity with drugs such as tamoxifen or fulvestrant and using aromatase inhibitors . Tumor growth can also be sustained by PR activation, and some ETs have been developed to target this receptor. The most common progestins used for BC treatment, particularly at advanced stages, comprise megestrol acetate and medroxyprogesterone acetate (MPA), while antiprogestins (e.g., RU486 or mifepristone, and onapristone) have been used in clinical trials, but they are still not an option in the clinic. Moreover, recent findings from the MIPRA window of opportunity clinical trial support the use of mifepristone in patients with luminal breast cancer with high PR isoform A/isoform B ratios . However, most BC patients initially respond to ET but eventually relapse (acquired resistance) and about 20–30% do not respond ( de novo resistance) .…”
Section: Introductionmentioning
confidence: 99%